A DC/DC Converter for 400 V and 800 V EVs Fast Charging Stations - Brajhan Benites Quispe, Jhon [UNESP] (2023)
This paper presents a DC/DC converter, which can be used in 400 V and 800 V EVs fast charging stations. The proposed topology is based on the conventional PSFB converter with a simples clamping circuit, and a auto-configurable output switching mechanism. This converter can operate under high power conversion efficiency because it had zero-voltage switching for primary power switches and soft-commutation for output rectifiers. Also, this proposal uses SiC MOSFET to reduce losses and improve converter performance. In addition, the proposed topology does not require any snubber circuits to reduce the voltage stress of the switching devices because the switch voltage of the primary and secondary power stage is confied by the input and clamping circuit voltage, respectively. Finally, the simulation results show the reliability of this design method.